Effect of Word-of-Mouth on Customer Patronage Intentions of Financial services: the moderation role of Corporate Image - Francis Osei; Collins Kankam-Kwarteng; Beverley Wilson-Wünsch (International Journal of Business and Development Studies)
Purpose – The purpose of this paper is to examine the relationships between word of mouth, corporate image and customer patronage intentions of financial services.Design/methodology/approach – The research analyses whether word of mouth and corporate image are predictors of patronage intentions. Specifically, the paper examines the moderating effects of corporate image in the relationship between word of mouth and patronage intentions using structural equation model. Data were collected from 848 customers selected from financial services firms. Exploratory and confirmatory factors analysis was performed on the study items after which the hypotheses were tested.Findings – The findings suggest that word-of-mouth has a significant impact on customer patronage intentions and corporate image also has significant influence on patronage intentions. Corporate image was found to moderate the relationship between word of mouth and patronage intentions. This indicates that word of mouth and corporate image are central to customer patronage intentions towards financial services.Research limitations/implications – There are limitations of the research. The first significant limitation is that the variables had various sub-dimensions. The second limitation is about sampling of the participants to represent all the customers of financial services in Ghana.Practical implications – This paper provides useful insights into financial service industry on the dimensions of word-of-mouth, corporate image, customer patronage intentions and how they are interrelated.Originality/value – the study of the interactive effects of word of mouth and corporate image on patronage intentions is unique and contributes to the explanation of customer behavior literature.